The frequency of smoking and depression and the contributing factors among municipal police officers - Kutlu, R.; Çivi, S.; Karaoğlu, O. (Journal of Dependence, 2008)
Objective: This study aimed to investigate the prevalence of smoking and depression among municipal police officers and the factors influencing these prevalence rates. Method: This descriptive, cross-sectional study was conducted among 157 municipal police officers working in the Konya Metropolitan Municipality. A questionnaire was administered to determine sociodemographic characteristics and smoking status. Data on depression were obtained using the Beck Depression Inventory (BDI). Findings: Of the study group, 99.4% were male (n=156), 79.6% (n=125) had secondary and high school education, 96.8% (n=152) were married and the mean age was 39.33±7.29 (min=22, max=57), 115 (73.2%) had chosen this profession willingly, 98 (62.4%) had been in court at least once during their career, 117 (74.5%) were in debt. The prevalence of current smoking was 49.1% (n=77), the prevalence of quitting smoking was 26.7% (n=42), and the prevalence of never smoking was 24.2% (n=38). The youngest age for starting smoking was 5, the oldest age was 40, and the median value was 18 years. Social factors were the most important factor in starting smoking (49.4%). According to the Beck Depression Inventory, 52.2% (n=82) were normal, 23.6% (n=37) were mildly depressed, 21.7% (n=34) were moderately depressed, and 2.5% (n=4) were severely depressed. Conclusion: Approximately half of the police officers in this study were current smokers and depressed. To prevent the negative effects of depression that may arise in the future among police officers, it is important to understand the origins of the stress factors currently prevalent. Furthermore, smoking cessation campaigns targeting police officers are urgently needed.
Keywords: cigaratte; depression